Toward a Free Platform for Financial Islamic Instruments: Analysis, Design and Development Special Case "MURABAHA" (The International Journal of Engineering & Information Technology (IJEIT), 2024)
the aim of this study is to analyze the informationsystem in Islamic bank by using Unified ModelingLanguage (UML). The major objective is to prepare thebackground for all actors working in Islamic bank tounderstand and use this free platform speciallyMURABAHA act.